Decreasing cytokeratin 17 expression in head and neck cancer predicts nodal metastasis and poor prognosis: The first evidence. (16th April 2018) - Xu, E.‐S.; Yang, M.‐H.; Liu, C.‐Y.; Liu, K.‐W.; Yang, T.‐T.; Chou, T.‐Y.; Hwang, T.‐Z.; Hsu, C.‐T.
Abstract : Objectives: Cytokeratins (CKs) are mainly expressed in epithelial carcinomas and are valuable for making diagnoses and identifying metastatic status. Changes in the expression of individual CKs in certain carcinoma may be relevant to establishing a prognosis. However, the prognostic significance of CKs in head and neck squamous cell carcinoma (HNSCC) remains elusive. Herein, we investigated the diverse and unique expression patterns of Cytokeratin 13 (CK13) and Cytokeratin 17 (CK17) and assessed the role of CK17 as a predictor for HNSCC metastasis and prognosis. Methods: CK13 and CK17 expressions were evaluated using immunohistochemical tissue microarray (TMA) analysis with 106 patients of HNSCC. To clarify the characterisation of CK17 expression with respect to its ability in predicting metastatic disease, an in vitro study of cells migration/invasion assays was conducted. Furthermore, the correlation of CK17 expression to clinicopathologic variables and prognosis was analyzed using a serial statistical method. Results: CK13 was predominately expressed in non‐cancerous tissues and was lost in HNSCC. Decreasing expression of CK17 correlated with cancerous cell migration and invasion ( P  <   .0001) in an in vitro study. CK17 expression was lower in the N1 and N2 nodal metastases category compared to the N0 stage. Moreover, Kaplan‐Meier survival analyses showed that a lower CK17 expression was associated with a poorer survival connotation in HNSCC patients ( P  <   .05) with 10‐year follow‐up. Conclusion: Our findings provide the first evidence that CK17 under‐expression might be a potential predictor of nodal metastasis and adverse prognosis.